SOURCES OF RESISTANCE AND TRICHOME ANALYSIS OF PHILIPPINE INDIGENOUS Hoya SPECIES AGAINST THE MILKWEED APHID, Aphis nerii Boyer De Fonscolombe (HEMIPTERA: APHIDIDAE) - Cris Cortaga (BIOTROPIA, 2023)
The Philippines is one of the centers of diversity of Hoya and an extensive collection of indigenous species are conserved at the Institute of Plant Breeding, University of the Philippines Los Baños. In maintaining these Hoya species inside the screenhouse, the major insect pest noted to attack the plants is the milkweed aphid, Aphis nerii Boyer de Fonscolombe. Thus, Hoyas were evaluated for resistance against this insect pest. Among the 45 Hoya species evaluated, 11 showed promising results wherein no aphid infestation was consistently observed during the three evaluation trials. These are H. aurigueana, H. carnosa, H. coriacea, H. diversifolia, H. greenii, H. imperialis, H. madulidii, H. obscura, H. odorata, H. paziae, and H. pubicalyx. As the first line of plants defense against herbivory, we sampled four resistant (H. madulidii, H. pubicalyx, H. carnosa, and H. obscura) and two susceptible (H. buotii and H. meliflua) species for analysis of their trichome traits. The mean trichome length was longest in H. carnosa (0.38mm), followed by H. madulidii (0.33mm), and lastly, H. pubicalyx and H. obscura (0.15mm). Mean trichome density (at 1.64mm2 microscopic field) was highest in H. madulidii (54.45), followed by H. pubicalyx (7.5), and lastly, H. carnosa (3.55) and H. obscura (3.45). In contrast, no trichome was observed in the susceptible species H. buotii and H. meliflua. Hence, trichomes are one of the important resistance traits of Hoya against the milkweed aphid. To our knowledge, this is the first report on resistance evaluation in Hoya and the role of its trichomes against the milkweed aphid. The results of this study can aide in the management of milkweed aphids and in developing improved Hoya cultivars with resistance to insects such as milkweed aphids.